2016
DOI: 10.1080/07448481.2016.1229320
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to meeting physical activity guidelines in active college students: A social cognitive perspective

Abstract: Results indicate that interventions designed to increase psychosocial factors may increase the likelihood of students meeting any and all PAGs. Social support may be especially beneficial for increasing muscle-strengthening activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Specifically, we examined four research questions related to PA trajectories (RQ1 and RQ2) and self-evaluation covariates (exercise self-efficacy, RQ3; anticipated shame, RQ4) over a 5-week period using latent growth modeling. Young adults, especially those who enroll in universities, are one segment of the population that typically experiences declines in PA ( Kwan et al, 2012 ) and often fail to meet recommended levels of PA ( Farren et al, 2017 ; American College Health Association, 2020 ). Major findings revealed considerable variation in young adults starting levels and trajectories of PA as well as consistent positive relations with exercise self-efficacy and inconsistent negative relations with anticipated shame.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, we examined four research questions related to PA trajectories (RQ1 and RQ2) and self-evaluation covariates (exercise self-efficacy, RQ3; anticipated shame, RQ4) over a 5-week period using latent growth modeling. Young adults, especially those who enroll in universities, are one segment of the population that typically experiences declines in PA ( Kwan et al, 2012 ) and often fail to meet recommended levels of PA ( Farren et al, 2017 ; American College Health Association, 2020 ). Major findings revealed considerable variation in young adults starting levels and trajectories of PA as well as consistent positive relations with exercise self-efficacy and inconsistent negative relations with anticipated shame.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence is robust across different demographics, time intervals, parameters of PA, study designs, and study contexts. For example, PA studies demonstrate that self-efficacy consistently enhances future PA in youth (Dishman et al, 2004), young adults (Parschau et al, 2012;Farren et al, 2017), adults (Dallow and Anderson, 2003), and older adults (Clark, 1996). However, Anderson-Bill et al (2011) revealed that exercise self-efficacy tends to decline with age.…”
Section: Self-evaluation and Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research used similarly constructed items to assess muscle-strengthening activity [39,40]. According to the PAGs to be categorized as meeting muscle-strengthening PAGs, participants needed to report doing muscle-strengthening activities on two or more days during the last 7 days [38].…”
Section: Physical Activity Profilementioning
confidence: 99%